A scientific community of digital heritage in time and space - Münster, Sander; Ioannides, Marinos (My University, 2015)
While both methodological discussions and proofs of concept including smaller samples were part of former publications, this paper presents first results from a bibliometric investigation of a large scale sample of more than 3,000 articles from major conferences dealing with digital heritage and covering the past two decades. This paper presents preliminary results from an investigation of nationalities of contributors, cross-national authorships, funding opportunities, as well as relevant topics and their evolution over time. Moreover, several discourse leading persons and institutions have been identified.
Keywords: Bibliometric; Bibliometrics; Cross-national; Digital heritage; Funding opportunities; Scientific community